KEDUDUKAN TERSANGKA DALAM PROSES PENYELIDIKAN DAN PENYIDIKAN TERDAPAT PELANGGARAN HAK-HAKNYA DILIHAT DARI ASPEK HUKUM PIDANA - Made Anwara (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThis study examines and addresses issues concerning the role of legal counsel in the investigation process; as well as the constraints faced by legal counsel in carrying out the defense in the investigation process.This study includes a descriptive type of empirical legal research. Research data using primary data and secondary data, primary data is original data obtained by researchers from the first hand from the main source in this case data obtained by the author from field research or research directly at Samarinda  Police Station and then also to the Legal Counsel who accompany suspect to know its role in process of investigation, secondary data is data obtained by researcher from library research and documentation which is result of research and processing of others who have been willing in the form of books or documentation usually provided in library. Sources of data in this study are secondary data sources consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques used are interview (interview) and literature study. Data analysis technique used is a qualitative data analysis that is a research procedure that produces analytical descriptive data that is what is expressed by respondents in writing or oral, and also the real behavior is researched and studied as something intact.The role of legal counsel in the investigation process that includes how the case of his position, because in the case of the position is threatened with the punishment of five years and above then must be accompanied by legal counsel. The legal advisor who accompanied the suspect was appointed by the investigator of the Samarinda  Police Resort through a letter of appointment which essentially contained a request to assist the suspect in the investigation process. Then on how the role of legal counsel in the investigation process that includes the rights, obligations, authority, steps, and actions in accompanying the suspect in the process of investigation. Then explained about the constraints faced by legal counsel in carrying out the defense in investigation process at Samarinda  Resort Police. Whereas the application of Article 115 of the legal advisors is only seen and heard only, and its presence only with the consent of the investigator whether allowing or not, if there is a matter that the legal advisors feel is not true then become a separate record for legal counsel to be submitted to the hearing. Investigators when using violence in obtaining information can be subject to Article 422 Penal Code and can be pre-trial.